Treatment of early stages of cervical cancer with radiation. - Majluf, Tewfick (2015)
It defined the early stages of uterine cancer discussing the theoretical and technical arguments militate in favor of radiotherapy, and concluded that the stadium "O" of cervical cancer could, by far, treated with radium uterovaginal ; stage 1 with radiotherapy alone or with radical surgery, with equal chances of success, according to the merits of each case; and stage II with radiation therapy alone or with preoperative radiotherapy. The initial stages of endometrial cancer should be treated with radium-uterovaginal followed by radical surgery until further notice. Has glimpsed the possibility of improving the current results as a result of advances in building megavoltage units, the technical improvement and knowledge in radiology.